One‐Step Production of 1, 3‐Butadiene from 2, 3‐Butanediol Dehydration. Issue 35 (26th July 2016) - Liu, Xi; Fabos, Viktoria; Taylor, Stuart; Knight, David W.; Whiston, Keith; Hutchings, Graham J.
Abstract: We report the direct production of 1, 3‐butadiene from the dehydration of 2, 3‐butandiol by using alumina as catalyst. Under optimized kinetic reaction conditions, the production of methyl ethyl ketone and isobutyraldehyde, formed via the pinacol–pinacolone rearrangement, was markedly reduced and almost 80 % selectivity to 1, 3‐butadiene and 1, 3‐butadiene could be achieved. The presence of water plays a critical role in the inhibition of oligomerization. The amphoteric nature of γ‐Al2 O3 was identified as important and this contributed to the improved catalytic selectivity when compared with other acidic catalysts. Abstract : The direct production of 1, 3‐butadiene from the dehydration of 2, 3‐butandiol by using alumina as catalyst is reported. Under optimized kinetic reaction conditions, the production of methyl ethyl ketone and isobutyraldehyde, formed via the pinacol–pinacolone rearrangement, was markedly reduced and almost 80 % selectivity to 1, 3‐butadiene could be achieved. The amphoteric nature of γ‐Al2 O3 was identified as important and this contributed to the improved catalytic selectivity when compared with other acidic catalysts.